Persepsi Pengunjung Objek Wisata Museum Sultan Mahmud Badaruddin II Palembang - Bagas Eka Saputra; Hadi Jauhari; Lisnini (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study aims to determine the visitor's perception of the marketing mix of product, price, location, promotion, people, process, and physical evidence. This study uses a qualitative research method with a descriptive quantitative approach with data collection techniques in the form of interviews with the main informants, observations and distribution of questionnaires to 100 respondents. Of the seven mixes, each of them got an average response of respondents' achievements that fall into the Good criteria, but only three of these 7 marketing mixes such as product mix, location and promotion have a significant effect on visitor perceptions.